Long-Term Blood–Brain Barrier Permeability Changes in Binswanger Disease. Issue 9 (September 2015) - Huisa, Branko N.; Caprihan, Arvind; Thompson, Jeffrey; Prestopnik, Jillian; Qualls, Clifford R.; Rosenberg, Gary A.
Abstract : Background and Purpose—: The blood–brain barrier (BBB) is disrupted in small vessel disease patients with lacunes and white matter hyperintensities (WMHs). The relationship of WMHs and regional BBB permeability changes has not been studied. We hypothesized that BBB disruption occurs in normal appearing WM and regions near the WMHs. To test the hypothesis, we repeated BBB permeability measurements in patients with extensive WMHs related to Binswanger disease. Methods—: We selected a subset of 22 Binswanger disease subjects from a well-characterized larger prospective vascular cognitive impairment cohort. We used 16 age-matched controls for comparison. The abnormal WM permeability (WMP) was measured twice for several years using dynamic contrast–enhanced magnetic resonance imaging. WMP maps were constructed from voxels above a predetermined threshold. Scans from first and second visits were coregistered. WM was divided into 3 regions: normal appearing WM, WMH ring, and WMH core. The ring was defined as 2 mm on each side of the WMH border. WMP was calculated in each of the 3 specific regions. We used paired t test, ANOVA, and Fisher exact test to compare individual changes. Results—: WMP was significantly higher in subjects than in controls ( P <0.001). There was no correlation between WMH load and WMP. High permeability regions had minimal overlap between first and second scans. Nine percent of WMP was within the WMHs, 49% within the normal appearing WM, and 52% within the WMH ring ( P <0.001; ANOVA). Conclusions—: Increased BBB permeability in normal appearing WM and close to the WMH borders supports a relationship between BBB disruption and the development of WMHs. Abstract : Supplemental Digital Content is available in the text.